HUMAN OF RESOURCE PLANNING IN FULFILLING THE NEEDS OF MEMBERS OF THE CIVIL SERVICE POLICE UNIT OF KUNINGAN DISTRICT, WEST JAVA PROVINCE - Rina Maulidah; Romli Arsad; Dyah Poespita E (Sean Institute, 2023)
Competent human reof sources are the main asset for an organization to achieve its established development goals. Human reof source planning is a systematic process examining the condition of human reof sources to ensure that the right number of skilled reof sources will be available when needed. This study analyzes human reof source planning in the Civil Service Police Unit of Kuningan District (Pamong Police Unit Praja Regency Kuningan) to improve organizational performance effectiveness. However, the Civil Service Police Unit of Kuningan District still faces various challenges, including a lack of adequate personnel to carry out their tasks, especially in dealing with complex situations requiring more human reof sources. The existence of contract-based employees (honorary employees) in meeting needs has attracted the attention of researchers. This research utilizes a qualitative method with a descriptive approach. This study carries out four stages of human reof source planning: job analysis, needs and workload analysis, recruitment and selection, and capacity development as the final stage. Data is collected through interviews with relevant parties, observations, and analysis of administrative regulations and government policies. The study results indicate a mismatch between government policies and administrative regulations regarding appointing personnel in the Civil Service Police Unit of Kuningan District. Additionally, there are limitations in budget allocation for capacity development implementation. These factors affect the effectiveness of human reof source planning in the organization. Based on these findings, it is recommended that the Civil Service Police Unit of Kuningan District pay attention to factors influencing human reof source planning and align them with government policies and administrative regulations. Moreover, there is a need for adequate budget allocation for the implementation of human reof source development to enhance the organization's performance and effectiveness in carrying out its tasks.